Calcification of the cavernosal bodies may be responsible for development of erectile dysfunction in uremic apolipoprotein E deficient (apoE-/-) mice - Ivanovski, Ognen; Nikolov, Igor G; Davceva, Olivera; Petrushevska, Gordana (Elsevier BV, 2019)
Erectile dysfunction's physiopathology in uremia is complex and multifactorial, involving a combination of classical risk factors and specific uremia-related risk factors such as increased oxidative stress, endothelial dysfunction and inflammation. The aim of the study is to investigate the effect of chronic kidney disease (CKD) on vascular calcification and endothelial function of cavernosal bodies in apolipoprotein E deficient (apoE-/-) mice, a well known model of erectile dysfunction.